(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Pilonidal sinus disease (PSD) is a chronic, inflammatory condition that typically affects the natal cleft of the sacrococcygeal region, occurs more commonly in young males. There is formation of sinus tracts that may contain hair and debris, often leading to infection, abscess formation, or chronic discharge. There are many nonsurgical and surgical techniques in the treatment of pilonidal sinus disease. This was a comparative study between two surgical techniques- Karydakis flap repair and Limberg flap repair in patients of pilonidal sinus. Material and methods: This prospective comparative study was conducted in the Department of General Surgery at Government medical college Patiala and Rajindra Hospital, from August 1, 2023 to July 31, 2024. The current study evaluated 60 patients diagnosed with sacrococcygeal pilonidal sinus disease, evenly divided between two surgical technique groups: Karydakis flap repair (Group A) and Limberg flap repair (Group B). The study aimed to evaluate and compare the operative durations, length of hospital stay, postoperative wound complications and wound healing time between the Karydakis flap repair and the Limberg flap repair in patients diagnosed with pilonidal sinus disease. All patients participating in the study were thoroughly informed about the procedure prior to surgery, and written informed consent was obtained from each individual. Results: The mean age was 29.1 ± 6.1 years with majority of patients were male, accounting for 90% of the total sample, while females represented 10%. The mean operative time was 41.9 ± 6.3 min in Karydakis flap (KF) repair and 46.5 ± 7.1 min in Limberg flap (LF) repair (p=0.03). Wound healing was faster in KF (11.6 ± 1.8 days) compared to LF (13.1 ± 2.1 days, p=0.02). However, postoperative complications were higher in KF (infection 20%, dehiscence 13.3%) compared to LF (infection 6.7%, dehiscence 3.3%, p=0.04). At 6-month follow-up, recurrence was seen in 3 cases (10%) in KF group, while none were reported in LF group. Conclusion: In conclusion, both the Limberg and Karydakis procedures are safe and effective surgical options for managing pilonidal sinus disease, showing comparable hospital stays and similar impacts on patients’ productivity. However, the Karydakis flap appears to be associated with a higher rate of postoperative infections, making the Limberg procedure more favorable in terms of short-term outcomes. To determine the definitive superiority of either technique requires evaluation of long-term outcomes as our findings are based solely on early postoperative outcomes. Further research with larger sample sizes and long-term follow-up is recommended to validate these results and assess long-term outcomes.